Improvement of the antibacterial activity of sesquiterpene lactones - Cartagena, Elena (2008)
Thirty six sesquiterpene lactones of the guaianolide and germacranolide-type from species of the Tribes Heliantheae and Vernonieae (Asteraceae) were evaluated for their antibacterial action. Thirty of them exhibited selective antibacterial activity, in hole-plate diffusion and liquid media assays, against two strains of Staphylococcus aureus and one of Enterococcus faecalis but resulted inactive on Lactobacillus paracasei, L. plantarum ,Escherichia coli , and Pseudomonas aeruginosa . The most active antibacterial compound was a melampolide-type sesquiterpene lactone, with a MIC = 78 microg/mL, against a methicillin-resistant S. aureus strain. An experimental strategy was also introduced to evaluate the effects of UV light on bacterial growth when certain sesquiterpene lactones were incorporated in hole-plate diffusion assays. Programmed UV irradiation (320-380 nm) during the first two hours of incubation of the agar plates produced increments of the antibacterial activity as a result of the incorporation of certain a, b -unsaturated lactones. In addition, an innovative method to increase the bioavailability of sesquiterpene lactones in antibacterial assays carried out in liquid media is also described. In fact, when polyethyleneglycol 400 (PEG 400) was incorporated (2.5%) to the bacterial cultures, an increment of the antibacterial activity was observed. Finally, hydrogenation of a natural sesquiterpene lactone gave two synthetic analogs whose antibacterial properties were also evaluated in order to set structure-activity relationships.